Risk Factors of Diabetes Mellitus among Saudi Patients above 40 Years in Dahda Area - Wijdan Saleh Abdullah, Mansour Ahmed Mohammed AL Makrami, Malak Saleh Abdullah,; Bayan Nassir Asseri, Ahlam Ahmed Abu Melha, Rawan Mari Alshehri,; Saleh Saeed Rashed, Sarah Abdullah Soliman, Kawther Mohammed Alajmi,; Fatimah Nassir Alsadiq, Abrar Abdu Abodayah, Moneerah Ali Assiri, (International Journal of Innovative Research in Medical Science, 2017)
Diabetes mellitus (DM) is a syndrome of chronic hyperglycaemia due to relative insulin deficiency, resistance, or both. It affects more than 120 million people world-wide, and it is estimated that it will affect 370 million by the year 2030. Diabetes is usually irreversible and, although patients can have a reasonably normal lifestyle, its late complications result in reduced life expectancy and major health costs. These include macrovascular disease, leading to an increased prevalence of coronary artery disease, peripheral vascular disease and stroke, and microvascular damage causing diabetic retinopathy and nephropathy. Neuropathy is another major complication.[1] A facility and community - based descriptive case study will be conducted in Dahda area and the Primary Health Care Center that related to this area to determine the risk factors of diabetes mellitus among people above 40 years old . Purposive and selective non-probability sampling techniques will be using for the selection of 55 diabetic patients. These include male and female Saudi. The data will be collected by questionnaires, the check lists, and interview interviews. The combined data revealed that the family history has a relationship with diabetes mellitus as it affect72.72% of diabetic patients and just 27.28% are not affected, the obesity is absent in 63.64 %, but it is present in 36.36%, the physical inactivity lead to the diabetes mellitus in 81.81% while 18.19 is not affected, The pregnancy affects 12.72% and not affects 87.28% of the diabetic women and effect of hypertension on diabetes mellitus in Dahda is 16.36% while 83.64% not affected. In this study we recommended that people must practice the sports at least one hour each day to control the diabetes mellitus or to prevent occurrence of diseases. In addition, they must eat the healthy diet and avoid the fatty food while they should reduce their weights if they are obese. Also, they are in a need to consult a physician to control their diabetes.